Studies about subject analysis in Brazil: Research and future perspectives - Dal'Evedove, Paula Regina; Tartarotti, Roberta Cristina Dal'Evedove [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2018)
The present study aims to map and discuss the knowledge produced on the subject analysis in Brazilian Information Science. For that, a bibliographic research was carried out by means of the survey of scientific articles published in national journals of the area of Information Science, using search terms: subject analysis and conceptual analysis. The analysis of the research corpus provided, among others, the identification of the theoretical referents in this universe and the current trends in the national literature of Information Science, which allowed to outline a panorama of the main challenges and future perspectives of research and development in subject analysis.
Estudos sobre análise de assunto no Brasil: Estado da arte e perspectivas futuras
Keywords: Brazil; Research; State of the art; Subject analysis